High-pressure low-degassing XLPE (cross linked polyethylene) as well as application and preparation method thereof in cable insulation material

By reducing the amount of peroxide crosslinking agent used in XLPE insulated cables and using accelerator and grafting additives, the impact of by-products on the insulation performance of the cable is solved, and the by-product content and methane gas concentration is reduced, thereby improving the performance and production efficiency of the cable.

CN119569950APending Publication Date: 2025-03-07JIANGSU SHANGSHANG CABLE GRP NEW MATERIAL CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411699667.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The presence of by-products such as methane, acetophenone and cumyl alcohol in existing XLPE insulated cables results in unstable cable insulation performance, affecting product usage performance, and degassing of by-products increases cost and time.

Method used

The crosslinking efficiency is improved and the generation of by-products is reduced by reducing the amount of peroxide crosslinking agent and grafting aids, such as allyl structured crosslinking agents and silane coupling agents.

Benefits of technology

A significant reduction in by-product content was achieved, with methane gas concentration as low as 123ppm and a by-product content reduced by at least 50%, while shortening the degassing treatment time and improving the mechanical and electrical properties of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569950A_ABST
    Figure CN119569950A_ABST
Patent Text Reader

Abstract

The high-pressure low-degassing XLPE is prepared from the following raw materials in parts by mass: 100 parts of polyethylene, 0.1 to 0.5 part of an antioxidant, 0.4 to 1.2 parts of a cross-linking agent, 0.1 to 0.8 part of an assistant cross-linking agent and 0.1 to 0.8 part of a grafting aid, the cross-linking agent is a peroxide cross-linking agent; and the grafting auxiliary agent is a silane grafting auxiliary agent. The high-pressure low-degassing XLPE is used as a cable insulation material. After the high-pressure low-degassing XLPE raw materials are weighed according to the formula, the preparation method comprises the following steps: putting the polyethylene and the antioxidant into an internal mixer for fully mixing; after the mixing is finished, extruding and granulating the material; dehydrating and drying the obtained material; and fully mixing the dried granules with a cross-linking agent, an assistant cross-linking agent and a grafting aid, carrying out post-absorption treatment, and cooling the material to obtain the product. According to the scheme, the dosage of the peroxide cross-linking agent is reduced from the formula, so that the content of by-products is fundamentally reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, in particular to a high-pressure low-degassing cross-linked polyethylene XLPE and its application in cable insulation material and a preparation method. Background Art

[0002] Cross-linked polyethylene (XLPE) insulated power cables are widely used due to their superior electrical properties and excellent properties in processing, laying, and easy use. With the continuous improvement and upgrading of XLPE insulation materials, XLPE insulated power cables have developed towards ultra-high voltage, large length, large cross-section and high reliability. Due to the particularity of the production process, chemical cross-linking has irreplaceable advantages over other cross-linking methods in medium-high voltage and large-section cables. Chemical cross-linking is the use of chemical cross-linking agents to cross-link polymers, transforming the linear structure into a mesh structure. Its mechanism is that the cross-linking agent (commonly used peroxides, such as diisopropylbenzene peroxide DCP) decomposes under the action of heat to generate active free radicals, which generate active points on the carbon chain of the polymer, thereby generating carbon-carbon cross-linking. In the peroxide cross-linking process, by-products are produced, including some volatile, flammable and unstable substances, mainly low-boiling point small molecules such as acetophenone, cumyl alcohol, methane and water, which are the main factors causing the instability of cable insulation performance and affecting the performance of the product. Among them, methane must be removed. It will be released along the longitudinal and radial directions of the cable, continuously accumulating a certain pressure, affecting the performance of the cable. When the methane gas reaches a certain concentration, it will burn, endangering human health and safety.

[0003] As the voltage level increases, the insulation thickness is also increasing. Some by-products will remain in the thick insulation layer, which will seriously affect the electrical performance of the cable. Acetophenone, cumyl alcohol and water will increase the resistance of the shielding layer and have an adverse effect on the insulation. The presence of such by-products will inhibit the internal conductivity and electron emission of tiny micropore defects, reduce the size of micropores, or fill the poor micropores in the insulation, to a certain extent, improve the breakdown strength of poor insulation, or cover up partial discharge, which will make the finished cable partial discharge and withstand voltage test lose authenticity. However, when the cable is powered on, the by-products are extremely unstable and detach from the cable to cause accidents.

[0004] A large number of research results show that the concentration of cross-linking by-products is directly determined by the content of peroxide cross-linking agent in the insulating material, and it is of great significance to adopt appropriate methods to reduce the concentration or proportion of by-products to a certain extent.

[0005] In order to reduce the impact of by-products on the performance of finished cables, technicians often use methods such as adjusting cable processes and degassing heat treatment of finished products to reduce the concentration of by-products. For example, reducing the production speed can allow the cable core to have a certain amount of time to volatilize by-products during the cross-linking process, but reducing the production speed sacrifices production capacity. Similarly, this method has a very limited effect on reducing by-products. Therefore, degassing heat treatment of cable cores is currently a commonly used method to reduce the concentration of by-products. Research results show that heat treatment of the produced XLPE insulated cores in a 60-70°C drying room for 2-4 days can remove low-molecular cross-linking by-products in the cable, reduce the accumulated charge in the insulating medium, and improve the electrical safety and mechanical properties of the cable.

[0006] There are also discussions in the prior art about cross-linked polyethylene with reduced cross-linking agent content. For example, the raw materials of "a kind of scorch-resistant high-cross-linking degree chemical cross-linked polyethylene insulation material and preparation method" disclosed in CN109370003A include (by weight): 80-120 parts of low-density polyethylene, 1.0-1.5 parts of cross-linking agent, 0.1-0.4 parts of antioxidant, and 0.2-0.4 parts of auxiliary cross-linking agent. The characteristics of this insulation material formula are low cross-linking agent content, and auxiliary cross-linking agent is used to increase the cross-linking degree of the insulation material. However, the amount of cross-linking agent and auxiliary cross-linking agent is still relatively high. At the same time, it can also be seen that in cross-linked polyethylene insulation material, the amount of cross-linking agent is difficult to further reduce.

[0007] Although degassing heat treatment can remove by-products and reduce the impact of by-products on material properties, the construction cost, electricity cost, and manpower of the drying room all add extra costs. In addition, degassing heat treatment reduces production efficiency. If the by-product concentration of the material itself can be reduced, the cost of degassing heat treatment will be greatly reduced, and even if the by-product concentration can be reduced to a certain extent, degassing can be achieved. Reducing the content of by-products can also ensure the excellent physical, mechanical and electrical properties of XLPE. Summary of the invention

[0008] In order to solve the above problems existing in the prior art, this technical solution proposes to reduce the amount of peroxide used in the XLPE formula, thereby fundamentally reducing the by-product content to obtain a low-degassing XLPE that can be used in power cable insulation materials. The specific technical solution is described as follows:

[0009] The invention belongs to the technical field of cable materials and relates to a high-pressure low-degassing XLPE. The XLPE is used as a cable insulating material.

[0010] The raw materials of high pressure low degassing XLPE include:

[0011] Polyethylene 100 parts,

[0012] 0.1-0.5 parts of antioxidant,

[0013] 0.4-1.2 parts of crosslinking agent,

[0014] 0.1 to 0.8 parts of auxiliary crosslinking agent,

[0015] Grafting aid 0.1-0.8 parts;

[0016] The crosslinking agent is a peroxide crosslinking agent; and the grafting auxiliary agent is a silane grafting auxiliary agent.

[0017] Furthermore, the polyethylene is low-density polyethylene, and the melt index of the low-density polyethylene is 1-5 g / 10 min (190° C. / 2.16 kg), and the melting point is 100-130° C.

[0018] The auxiliary cross-linking agent is an auxiliary cross-linking agent containing an allyl structure, that is, contains an allyl group.

[0019] The grafting auxiliary agent is a silane coupling agent, and the compound has the property of homopolymerization or grafting onto a polymer chain.

[0020] The general formula of the silane coupling agent used as a grafting aid is R n SiX (4-n) , wherein R is a non-hydrolyzable organic functional group that can be combined with a high molecular polymer, and X is a hydrolyzable group.

[0021] The R is a methyl group, a vinyl group, an amino group, an epoxy group, a mercapto group or an acryloxypropyl group; and X is an alkoxy group, an aryloxy group, an acyl group or a chloro group.

[0022] The preferred formula is: 100 parts of polyethylene, 0.1-0.5 parts of antioxidant, 0.4-0.6 parts of cross-linking agent, 0.1-0.8 parts of auxiliary cross-linking agent, and 0.1-0.4 parts of grafting auxiliary agent.

[0023] Specifically:

[0024] The crosslinking agent is one or more of diisopropylbenzene peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (bis-25), and di-tert-butyl peroxide (BIBP);

[0025] The auxiliary cross-linking agent is triallyl isocyanurate (TAIC) and / or triallyl urate (TAC);

[0026] The antioxidant is one or more of antioxidant 300 (4,4'-thiobis(6-tert-butyl-3-methylphenol)), antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), antioxidant 1076 (n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite).

[0027] High-pressure low-degassing XLPE is used for cable insulation material. The preparation method thereof comprises the following steps: after the high-pressure low-degassing XLPE raw material is weighed according to a formula, the preparation steps include: putting polyethylene and an antioxidant into an internal mixer and fully mixing them; after the mixing is completed, the material is extruded and granulated; the obtained material is dehydrated and dried; the dried granules are fully mixed with a cross-linking agent, a co-cross-linking agent and a grafting auxiliary agent and subjected to a post-absorption treatment, and the material is cooled to obtain a product.

[0028] Specifically: weigh the raw materials according to the formula, and then prepare according to the following steps:

[0029] S1: Put polyethylene and antioxidant into internal mixer and mix them thoroughly; after mixing, the materials are extruded and granulated;

[0030] S2: Dehydrating and drying the material obtained in step S1;

[0031] S3: fully mixing the pellets obtained in step S2, the crosslinking agent, the auxiliary crosslinking agent and the grafting auxiliary agent;

[0032] S4: performing post-absorption treatment on the pellets obtained in step S3; cooling the material after the post-absorption treatment to obtain a low degassing insulating material.

[0033] Preferably, in step S1, the mixing temperature is 170°C, the time is 5 to 10 minutes; the extrusion temperature is 170°C;

[0034] In step S3, the mixing temperature is 40 to 70° C. and the time is 5 to 10 minutes;

[0035] In step S4, the post-absorption temperature is 40-70° C. and the time is 2-24 h.

[0036] The high-voltage low-degassing XLPE obtained according to the formula of the present invention has excellent mechanical properties and electrical properties, and is particularly suitable for cable insulation. The content of cross-linked byproducts of the low-degassing XLPE can be as low as 0.6%, and the content of characteristic gas methane in the byproducts can be as low as 123ppm. The low-degassing XLPE insulation material can be applied to medium and high voltage power cables. Compared with other low-degassing XLPE cables (the content of insulation byproducts is generally 1.2-1.9%, and the degassing time is 3-7 days), the byproduct content can be reduced by at least 50%, and the degassing time is shortened to 1 day (the methane gas content is less than 100ppm).

[0037] The principles and beneficial effects of the present invention are described as follows:

[0038] The high-voltage, low-degassing XLPE obtained by adopting the above technical solution is suitable for insulating cable materials. The cable material has a low by-product content and methane gas concentration, which can effectively improve the production efficiency of cable materials, reduce the degassing treatment time and cost, and at the same time, the cable material has excellent mechanical and electrical properties and can be used in medium and high voltage insulating materials for power cables.

[0039] In order to effectively reduce the content of cross-linking by-products during the cross-linking process, this solution starts from the root and reduces the content of by-products by reducing the content of cross-linking agents. By adding co-cross-linking agents and grafting aids, high cross-linking efficiency is achieved at low cross-linking agent content. The insulating material has excellent mechanical properties, and the reduction of by-products also ensures the electrical properties of the material.

[0040] In order to reduce the amount of cross-linking agent used, the cross-linking aid used in this solution contains an allyl group, which can form reactive free radicals under high temperature conditions and only has an effect on the degree of cross-linking. It can accelerate the cross-linking speed by abstracting hydrogen to form free radicals, reduce the decomposition temperature of the peroxide cross-linking agent, and improve the cross-linking efficiency of the peroxide. This type of cross-linking aid does not produce additional gas by-products, so adding a certain amount of cross-linking aid can effectively reduce the content of the peroxide cross-linking agent, thereby achieving the purpose of reducing the content of cross-linking by-products.

[0041] In order to further reduce the amount of cross-linking agent used, the grafting aid used in this scheme is a silane coupling agent. Under high temperature conditions (170-210°C) and in the presence of a peroxide cross-linking agent, this type of aid will undergo a grafting reaction with the polyethylene molecular chain. During the grafting reaction, the polyethylene macromolecule loses hydrogen atoms under the action of peroxide to form free radicals. The free radicals react with the polar groups in the molecule to undergo chain transfer, grafting the aid onto the polyethylene molecular chain, that is, reacting with the hydrogen atoms on the polymer macromolecular chain to form macromolecular free radicals. These macromolecular free radicals then undergo a coupling reaction, that is, two macromolecular free radicals combine to form cross-linking bonds, thereby enhancing the network structure of the polymer; in addition, the grafted macromolecules, because they have a silane structure, can also react with the by-product water produced during the peroxide cross-linking process, thereby causing cross-linking between the macromolecules to form a network structure. As the silane content increases, the degree of the entire cross-linking reaction becomes more intense. Specific details are attached. Figure 1 (DSC temperature rise enthalpy change curve under different grafting agent contents) and Appendix 1. Therefore, the silane coupling agent can effectively increase the number of cross-linking points, and a high cross-linking density of the material can also be achieved at a low cross-linking agent content.

[0042] The main problems caused by improper use of grafting aids or no use of grafting aids include insufficient cross-linking degree of XLPE, which manifests as poor thermal elongation, and at the same time, the thermal aging performance, electrical properties and other properties of XLPE are reduced.

[0043] In this scheme, by adding silane grafting aid, the amount of crosslinking agent used is reduced. For 100 parts by mass of polyethylene, the crosslinking agent content can be as low as 0.4 parts, which can ensure that the material is fully crosslinked. The reduction in the amount of peroxide crosslinking agent used will reduce the content of by-products during production. On the one hand, it can shorten the degassing heat treatment time of cable materials after production. On the other hand, low by-products will also mean fewer defects in the material due to the release of by-products, which is conducive to improving the electrical properties of the material.

[0044] Table 1 The change of exothermic enthalpy during crosslinking with the content of grafting additives

[0045] Grafting agent content 0phr 0.2phr 0.4phr 0.6phr 0.8phr Enthalpy change J / g 3.70 4.28 5.61 7.37 12.66 BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is the DSC temperature rise enthalpy change curve (high temperature cross-linking process of insulating materials with different grafting agent contents, center temperature 175°C). DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with specific embodiments.

[0048] The invention discloses a low-degassing XLPE, which can be used for insulating cable materials. The low-degassing XLPE comprises the following raw materials by weight: 100 parts of polyethylene, 0.1 to 0.5 parts of antioxidant, 0.4 to 1.2 parts of cross-linking agent, 0.1 to 0.8 parts of auxiliary cross-linking agent, and 0.1 to 0.8 parts of grafting auxiliary agent; the cross-linking agent is a peroxide cross-linking agent;

[0049] The auxiliary cross-linking agent is a type of cross-linking auxiliary agent containing an allyl structure, such as one or more of triallyl isocyanurate (TAIC), triallyl urate (TAC), etc.;

[0050] The grafting aid is a silane coupling agent.

[0051] The polyethylene is low-density polyethylene, and the melting index of the low-density polyethylene is 1-5 g / 10 min (190° C. / 2.16 kg) and the melting point is 100-130° C.

[0052] The crosslinking agent is any one or two of dicumyl peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (bis-25), and di-tert-butyl peroxide (BIBP).

[0053] The grafting aid is a silane coupling agent grafting aid, which has the characteristics of homopolymerization or grafting onto the polymer chain.

[0054] The antioxidant is used to prevent polyethylene from aging under the action of thermal oxidation, and is selected from one or more of antioxidant 300 (4,4'-thiobis(6-tert-butyl-3-methylphenol)), antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol), antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and antioxidant 168 (tris(2,4-di-tert-butylphenyl) phosphite).

[0055] Cross-linking agents are used to cross-link polyethylene, causing chemical reactions in the molecules inside the polyethylene, connecting the molecules with chemical bonds to form a three-dimensional network structure. Co-cross-linking agents are used to accelerate the speed of the cross-linking reaction and promote the formation of the cross-linked structure of polyethylene. Grafting aids can be homopolymerized or grafted onto polymer chains, while ensuring the cross-linked network of polyethylene, reducing the amount of cross-linking agent used.

[0056] The preparation method of the high-pressure low-degassing XLPE of the present invention is to first weigh the raw materials according to the formula, and then prepare according to the following steps:

[0057] S1: Put polyethylene and antioxidant into internal mixer and mix them thoroughly; after mixing, the materials are extruded and granulated;

[0058] S2: Dehydrating and drying the material obtained in step S1;

[0059] S3: fully mixing the pellets obtained in step S2 with the cross-linking agent, the auxiliary cross-linking agent and the grafting auxiliary agent;

[0060] S4: The pellets obtained in step S3 are subjected to post-absorption treatment in a high-speed mixer; the material after the post-absorption treatment is cooled to obtain the desired product.

[0061] In this example, in step S1, the mixing temperature is 170°C and the time is 5 to 10 minutes; the extrusion temperature is 170°C; in step S3, the mixing temperature is 40 to 70°C and the time is 5 to 10 minutes; in step S4, the post-absorption temperature is 40 to 70°C and the time is 2 to 24 hours.

[0062] The present invention is further described below in conjunction with specific embodiments.

[0063] The raw material information involved in this embodiment is as follows

[0064]

[0065]

[0066] The high-voltage low-degassing XLPE cable insulation material of Example 1 comprises the following components in parts by weight:

[0067] 100 parts of polyethylene 220HEC, 0.2 parts of antioxidant 300, 0.6 parts of crosslinking agent bis 25, 0.4 parts of auxiliary crosslinking agent TAIC, and 0.2 parts of grafting auxiliary silane coupling agent KH-580.

[0068] The following preparation process is used for preparation:

[0069] S1: First, polyethylene and antioxidant are put into an internal mixer for mixing at a temperature of 170°C for 8 minutes. After mixing, the materials are filtered and extruded into granules through a twin-screw extruder at a temperature of 170°C.

[0070] S2: Dehydrating and drying the material obtained in step S1;

[0071] S3: mixing the pellets obtained in step S2 with a crosslinking agent, a co-crosslinking agent and a grafting aid at a mixing temperature of 70° C. for 10 min;

[0072] S4: The pellets obtained in step S3 are subjected to post-absorption, and the material after the post-absorption treatment is cooled to obtain a low degassing XLPE insulating material, the post-absorption temperature is 70° C., and the time is 8 hours.

[0073] Example 2 is basically the same as Example 1, except that the grafting aid KH580 is 0 parts in the raw material.

[0074] Example 3 is basically the same as Example 1, except that the raw material contains 0.4 parts of grafting aid KH580.

[0075] Example 4 is basically the same as Example 1, except that the grafting aid KH580 is 0.6 parts in the raw material.

[0076] Example 5 is basically the same as Example 1, except that the grafting aid KH580 is contained in the raw material in an amount of 0.8 parts.

[0077] Example 6 is basically the same as Example 1, except that the grafting aid KH580 in the raw material is replaced by KH570 in equal amounts.

[0078] Example 7 is basically the same as Example 1, except that the grafting aid KH580 in the raw material is replaced by KH550 in equal amounts.

[0079] Example 8 is basically the same as Example 1, except that the content of cross-linking agent di-25 in the raw material is 0.4 parts.

[0080] Example 9 is basically the same as Example 1, except that the content of crosslinking agent bis 25 in the raw material is 1.2 parts

[0081] Example 10 is substantially the same as Example 1, except that the crosslinking agent bis-25 in the raw material is replaced by DCP in equal amounts.

[0082] Example 11 is basically the same as Example 1, except that the cross-linking agent Bis-25 in the raw material is replaced by BIBP in equal amounts.

[0083] Example 12 is basically the same as Example 1, except that the content of antioxidant 300 in the raw material is 0.1 parts.

[0084] Example 13 is basically the same as Example 1, except that the content of antioxidant 300 in the raw material is 0.5 parts.

[0085] Example 14 is substantially the same as Example 1, except that the antioxidant 300 in the raw materials is replaced by 0.2 parts of antioxidant 1010 and 0.1 parts of antioxidant 168.

[0086] Example 15 is substantially the same as Example 1, except that the antioxidant 300 in the raw materials is replaced by 0.2 parts of antioxidant 1076 and 0.1 parts of antioxidant 168.

[0087] Example 16 is basically the same as Example 1, except that the content of the auxiliary cross-linking agent TAIC in the raw material is 0.1 parts.

[0088] Example 17 is basically the same as Example 1, except that the content of the auxiliary cross-linking agent TAIC in the raw material is 0.8 parts.

[0089] The formulas for each example are as follows

[0090]

[0091]

[0092] Performance testing:

[0093] The insulating material obtained in the embodiment is placed in a flat vulcanizer for sheeting. The vulcanization temperature is 180°C, the time is 15 minutes, the pressure is 15 MPa, and the vulcanization is cooled for 5 minutes. The samples of each embodiment are respectively tested for performance, tensile strength and elongation at break, heat aging test, heat extension test, dielectric strength, dielectric loss factor, volume resistivity, breakdown strength, degassing content and methane gas content. The data are shown in Table 2 and Table 3 respectively.

[0094] 1. Tensile strength and elongation at break test: refer to GB / T 2951.11-2008 "General test methods for insulation and sheath materials of electric and optical cables Part 11: General test methods - Thickness and dimensional measurement - Mechanical properties test" to test the tensile strength and elongation at break of the sample.

[0095] 2. Heat aging test: refer to GB / T 2951.12-2008 "General test methods for insulation and sheath materials of electric and optical cables Part 12: General test methods - Heat aging test methods" for testing; the heat aging conditions are: aging temperature is 135°C, aging time is 168h, then observe whether there are cracks on the appearance of the sample, and perform tensile strength and elongation at break tests, and calculate the change rate of tensile strength and elongation at break of the sample.

[0096] 3. Hot elongation test: refer to GB / T 2951.21-2008 "General test methods for insulation and sheath materials of electric and optical cables Part 21: Special test methods for elastomeric mixtures. Ozone resistance test-Hot elongation test-Mineral oil immersion test", test the elongation of the sample under load and the permanent deformation rate after cooling.

[0097] 4. Dielectric strength and dielectric loss factor: According to GB / T 1409-2006 standard: Recommended method for determining the permittivity and dielectric loss factor of electrical insulating materials at power frequency, audio frequency and high frequency.

[0098] 5. Volume resistivity: Test according to the method described in 31838.2-2019 "Dielectric and resistance properties of solid insulating materials Part 2: Resistance properties (DC method) Volume resistance and volume resistivity".

[0099] 6. Breakdown strength: Test in accordance with GB / T 1408-2006 “Electrical strength test method for insulating materials”.

[0100] 7. Degassing content: The experiment uses a blast drying oven to detect the degassing weight loss content of the cross-linked polyethylene sample. The degassing temperature is 70°C and the time is 72 hours.

[0101] 8. Methane gas content detection: The methane gas content is determined by gas chromatography-flame ionization detector using the external standard method.

[0102] Table 2

[0103]

[0104]

[0105] Table 3

[0106]

Claims

1. A high pressure low degassing XLPE, characterized in that: The raw materials include by weight: Polyethylene 100 parts, 0.1-0.5 parts of antioxidant, 0.4-1.2 parts of crosslinking agent, 0.1 to 0.8 parts of auxiliary crosslinking agent, Grafting auxiliary agent 0.1-0.8 parts; The crosslinking agent is a peroxide crosslinking agent; and the grafting auxiliary agent is a silane grafting auxiliary agent.

2. The high pressure low degassing XLPE according to claim 1, characterized in that The polyethylene is low-density polyethylene, and the melting index of the low-density polyethylene is 1-5 g / 10 min (190° C. / 2.16 kg) and the melting point is 100-130° C.

3. The high pressure low degassing XLPE according to claim 1, characterized in that The auxiliary cross-linking agent is an auxiliary cross-linking agent containing an allyl structure.

4. The high pressure low degassing XLPE according to claim 1, characterized in that The grafting aid is a silane coupling agent, which has the property of homopolymerizing or grafting onto the polymer chain.

5. The high pressure low degassing XLPE according to claim 4, characterized in that The general formula of the silane coupling agent used as a grafting aid is R n SiX (4-n) , wherein R is a non-hydrolyzable organic functional group that can be combined with a high molecular polymer, and X is a hydrolyzable group.

6. The high pressure low degassing XLPE according to claim 5, characterized in that The R is a methyl group, a vinyl group, an amino group, an epoxy group, a mercapto group or an acryloxypropyl group; and X is an alkoxy group, an aryloxy group, an acyl group or a chloro group.

7. The high pressure low degassing XLPE according to claim 1, characterized in that The crosslinking agent is one or more of diisopropylbenzene peroxide (DCP), 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (bis-25), and di-tert-butyl peroxide (BIBP); The auxiliary cross-linking agent is triallyl isocyanurate and / or triallyl cyanurate; The antioxidant is one or more of antioxidant 300 (4,4'-thiobis(6-tert-butyl-3-methylphenol)), antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), antioxidant 1076 (n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and antioxidant 168 (tris(2,4-di-tert-butylphenyl)phosphite).

8. The high pressure low degassing XLPE according to claim 1, characterized in that Used for cable insulation.

9. The high pressure low degassing XLPE according to claim 1, characterized in that The raw materials of the high pressure low degassing XLPE are weighed according to the formula and prepared according to the following steps: S1: Put polyethylene and antioxidant into internal mixer and mix them thoroughly; after mixing, the materials are extruded and granulated; S2: Dehydrating and drying the material obtained in step S1; S3: fully mixing the pellets obtained in step S2, the crosslinking agent, the auxiliary crosslinking agent and the grafting auxiliary agent; S4: performing post-absorption treatment on the pellets obtained in step S3; cooling the material after the post-absorption treatment to obtain a low degassing insulating material.

10. The high pressure low degassing XLPE according to claim 9, characterized in that In step S1, the mixing temperature is 170°C for 5 to 10 minutes; the extrusion temperature is 170°C; In step S3, the mixing temperature is 40 to 70° C. and the time is 5 to 10 min; In step S4, the post-absorption temperature is 40-70° C. and the time is 2-24 h.

Citation Information

Patent Citations

  • Scorch-resistant chemically-crosslinked polyethylene insulation material with high crosslinking degree and preparation method of scorch-resistant chemically-crosslinked polyethylene insulation material

    CN109370003A